Modulating the relaxation dynamics via structural transition from a dinuclear dysprosium cluster to a nonanuclear cluster. Issue 37 (8th September 2021) - Hu, Peng; Cao, Ling-hui; Liu, Ao-gang; Zhang, Yi-quan; Zhang, Tian-le; Li, Bao
Abstract : Along with the transition from a dinuclear dysprosium cluster to a nonanuclear one, variable magnetic relaxation with the energy barrier changing from 217.87 K to 9.24 K has been presented, which has been validated by ab initio calculations. Abstract : A dinuclear dysprosium cluster [Dy2 (NO3 )4 (H2 O)2 (L)2 ]·2CH3 CN was successfully prepared by employing HL (HL = 2, 6-dimethoxyphenol) and Dy(NO3 )3 ·6H2 O in a mixture of CH3 OH and CH3 CN. The conversion of this Dy2 compound by reaction with additional deprotonated ligand generated a Dy9 cluster [Dy9 (μ4 -OH)2 (μ3 -OH)8 (μ2 -OCH3 )4 (NO3 )8 (H2 O)8 (L)4 ](OH)·2H2 O with the well-known "diabolo" topology. Magnetic investigation revealed that both of the clusters exhibit typical SMM characteristics, and variable magnetic relaxation with the energy barrier changing from 217.87 K to 9.24 K along with the transition from a dinuclear dysprosium cluster to a nonanuclear one. Ab initio calculations further confirm the corresponding structure–activity relationships that originate the different magnetic behaviours. This design may afford a feasible strategy for modulating the magnetic relaxation dynamics of polynuclear systems.